Implementasi manajemen strategi dalam meningkatkan kinerja dan daya saing bank syariah di indonesia - Mukti, Fitri Ana (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the implementation of strategic management in improving the performance and competitiveness of Islamic banks in Indonesia. Using a descriptive qualitative approach through library research, data were obtained from national and international journals, as well as academic sources from UIN Malang. The findings reveal that the implementation of strategic management—covering formulation, implementation, and evaluation—enhances efficiency, profitability, and compliance with maqashid sharia. Supporting factors such as digital transformation, product innovation, risk management, and good corporate governance are crucial in strengthening the competitive position of Islamic banks in the global market. Moreover, the development of competent and ethical human resources plays a significant role in achieving long-term strategic success. Therefore, integrating business strategies with Islamic values forms the foundation for sustainability and social welfare within the Islamic banking industry.